Hubungan Antara Pengetahuan Ibu dan IMD Dengan Praktik ASI Eksklusif - Zuhud Nur Rosyid; Sri Sumarmi (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2017)
Background: Breast milk is the most appropriate food given to babies. Breast milk is the only drink or food that a baby needs at the age of 0-6 months first. Breast milk helps growth and development, contains anti-body and other essential nutrients that can protect babies from various diseases. In 2013, the exclusive breast milk presentation at Puskesmas Ayah I is 87.65%, decreasing in 2014 and 2015 become 78.26% and 71.65%. Many factors can influence the behavior of exclusive breastfeeding. Objectives: The purpose of this research was to analyze the relationship between mother knowledge and early breastfeeding initiation practice with exclusive breastfeeding prectices in the working area of Puskesmas Ayah I Kebumen Ditrict.Methods: The type of this research was quantitative using cross sectional design. This study was conducted from June-August of 2017. The population used was all mothers who were breastfeeding and had infants aged 6-11 months in three villages in the working area of Puskesmas Ayah I namely Tlagasari, Ayah and Bulurejo villages. Sampling by proportional random sampling method with sample size were 61 respondents. Data was analised by chi-square test.Results: The result showed that there was a relationship between mothers’s knowledge and exclusive breastfeding practice (p=0.000), and early breastfeeding initiation practice with Exclusive Breast-feeding practice (p=0.025)Conclusion: The mother's knowledge level on exclusive breastfeeding affects the success of exclusive breastfeeding practices. The existence of early initiation of breastfeeding practices by the mother, a greater chance in giving exclusive breastfeeding in infants.ABSTRAK Latar belakang : Air Susu Ibu (ASI) merupakan makanan yang paling tepat diberikan pada bayi. Air susu ibu satu-satunya minuman atau makanan yang diperlukan bayi pada usia 0-6 bulan pertama. ASI membantu pertumbuhan dan perkembangan, mengandung anti bodi dan zat gizi penting lainnya yang mampu melindungi bayi dari berbagai penyakit. Pada tahun 2013, cakupan ASI eksklusif di Puskesmas Ayah I sebesar 87, 65%, terjadi penurunan pada tahun 2014 dan tahun 2015 menjadi 78,26% dan 71,65%. Terdapat beberapa faktor yang berhubungan dengan perilaku pemberian ASI secara Eksklusif.Tujuan: Tujuan dari penelitian ini yaitu menganalisis hubungan antara pengetahuan ibu dan IMD dengan pemberian ASI secara eksklusif pada wilayah kerja Puskesmas Ayah I Kebumen.Metode : penelitian ini bersifat kuantitatif dengan desain cross sectional. Penelitian dilakukan bulan Juni sampai Agutus tahun 2017. Populasi dalam penelitian ini yaitu seluruh ibu yang pernah atau sedang menyusui dan memiliki bayi usia 6-11 bulan di desa Tlagasari, Ayah, dan Bulurejo Puskesmas Ayah I. Sampel diambil melalui metode proportional random sampling dan diperoleh sampel sebesar 61 responden. Analisis data menggunakan uji chi-square.Hasil : Bahwa ada hubungan yang bermakna antara pengetahuan ibu dengan pemberian ASI secara eksklusif (p=0,000), dan IMD dengan pemberian ASI secara eksklusif (p=0,025).Kesimpulan : Tingkat pengetahuan ibu mengenai ASI eksklusif berpengaruh terhadap keberhasilan praktik pemberian ASI eksklusif. Adanya praktik IMD oleh ibu, berpeluang lebih besar dalam memberikan ASI eksklusif pada bayi.